Shock treatment in a cohort of Scandinavian intensive care units in 2014. Issue 7 (12th June 2016) - Kollind, M.; Wickbom, F.; Wilkman, E.; Snäckestrand, M. S. C.; Holmén, A.; Oldner, A.; Perner, A.; Åneman, A.; Chew, M. S.; ,
Abstract : Background: Shock is common in intensive care units, and treatment includes fluids, vasopressor and/or inotropic drugs, guided by hemodynamic monitoring. The aim of this study was to identify current practice for treatment of shock in Scandinavian intensive care units. Methods: Seven‐day inception cohort study in 43 intensive care units in Scandinavia. Patients ≥ 15 years old receiving more than 4 h of cardiovascular acting drug infusion were included. The use of fluids, vasopressor and inotropic drugs, type of monitoring, and target values were recorded. Results: One hundred and seventy‐one patients were included. At inclusion, 136/168 (81%) had received vasopressor and/or inotropic drug therapy for less than 24 h, and 143/171 (84%) had received volume loading before the onset of vasoactive drug treatment. Ringer's solution was given to 129/143 (90%) of patients and starches in 3/143 (2%) patients. Noradrenaline was the most commonly used cardiovascular acting drug, given in 168/171 (98%) of cases while dopamine was rarely used. Mean arterial pressure was considered the most important variable for hemodynamic monitoring. Invasive arterial blood pressure was monitored in 166/171 (97%) of patients, arterial pulse wave analysis in 11/171 (7%), and echocardiography in 50/171 (29%). Conclusion: In this survey, Ringer's solution and noradrenaline were the most common first‐line treatments in shock. The use of starches and dopamine were rare. Almost all patients were monitored with invasive arterial blood pressure, but comprehensive hemodynamic monitoring was used only in a minority of patients.